2012
DOI: 10.1074/jbc.m112.341248
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-21 (FGF21) Regulates Low-density Lipoprotein Receptor (LDLR) Levels in Cells via the E3-ubiquitin Ligase Mylip/Idol and the Canopy2 (Cnpy2)/Mylip-interacting Saposin-like Protein (Msap)

Abstract: Background: LDLR is regulated by the E3 ubiquitin ligase Mylip/Idol. Results: FGF21 down-regulates Mylip/Idol expression and up-regulates its inhibitor Cnpy2/Msap. Conclusion: Increased LDLR by FGF21 results in increased lipoprotein uptake in human hepatocyte cells. Significance: The FGF21-mediated effect on cholesterol uptake is additive to that of statin, which may be of clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 34 publications
3
66
1
Order By: Relevance
“…Although we previously described polyclonal antibodies capable of detecting adenovirally expressed IDOL (5), we have been unable to consistently visualize endogenous or transfected protein with these reagents. Other IDOL antibodies have been described that recognize bands of ϳ51 kDa (26,27); however, the major proteins detected by these reagents are not responsive to LXR agonist or MG132 and were present in IDOL-null cells (see Fig. S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…Although we previously described polyclonal antibodies capable of detecting adenovirally expressed IDOL (5), we have been unable to consistently visualize endogenous or transfected protein with these reagents. Other IDOL antibodies have been described that recognize bands of ϳ51 kDa (26,27); however, the major proteins detected by these reagents are not responsive to LXR agonist or MG132 and were present in IDOL-null cells (see Fig. S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies by Zelcer et al 43 have indicated that shRNA-mediated targeting of MYLIP/IDOL mRNA is associated with increased LDL receptor protein expression and an enhanced LDL uptake in hepatocytes. Recent follow-up studies have shown that MYLIP/IDOL transcript levels can be modulated by fibroblast growth factor-21 55 and estrogen, 56 suggesting that MYLIP/IDOL expression may be highly responsive to changes in the body's hormonal balance. Although functional studies are necessary to prove a direct regulatory control of MYLIP/IDOL transcription by glucocorticoids, our studies at least hint to a potentially relevant link between the tissue glucocorticoid status and hepatic MYLIP/IDOL expression and thus indirectly the LDL receptor-mediated clearance of apolipoprotein B-containing lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured for 5-7 days and stimulated with 50 g/ml BDNF (PeproTech, London, United Kingdom) or with 0.1-2 g/ml recombinant Reelin (R&D Systems) alone or together for various periods of times. The synthetic liver X receptor (LXR) ligand GW3965 was used to induce Mylip/Idol (27,29), actinomycin D (Sigma) was used to inhibit gene transcription, and bafilomycin A 1 (Sigma) was used to block lysosomes. To down-regulate Mylip/Idol, freshly prepared neurons were transfected with Mylip shRNA constructs using the Nucleofector rat neuron system (Amaxa GmbH) as described previously (32,33).…”
Section: Methodsmentioning
confidence: 99%
“…Lysates from precleared cell supernatants were incubated overnight at 4°C on a rotary shaker using 2 g/ml anti-VLDLR antibodies. Immunocomplexes were bound to Sepharose A for 2 h at 4°C and recovered by centrifugation (29). Beads were washed three times, and the samples were resuspended in SDS-PAGE buffer and subjected to immunoblotting using anti-VLDLR and anti-ubiquitin antibodies.…”
Section: Methodsmentioning
confidence: 99%